Influence of Sound on Empirical Brain Networks - Sawicki, Jakub; Schöll, Eckehard (Frontiers in Applied Mathematics and Statistics, 2021)
We analyze the influence of an external sound source in a network of FitzHugh–Nagumo oscillators with empirical structural connectivity measured in healthy human subjects. We report synchronization patterns, induced by the frequency of the sound source. We show that the level of synchrony can be enhanced by choosing the frequency of the sound source and its amplitude as control parameters for synchronization patterns. We discuss a minimum model elucidating the modalities of the influence of music on the human brain.